2022
DOI: 10.1021/acsomega.2c04151
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Aza-BODIPYs, Their Differential Binding for Cu(II), and Results of Bioimaging as Fluorescent Dyes of Langerhans β-Cells

Abstract: Cellular labeling through the use of dyes is of great interest to the biomedical sciences for the characterization of the location and distribution of biomolecules and also for the tracking of the course of biological processes in both health and illness. This paper reports the synthesis, characterization, and subsequent evaluation as metal sensors and cell staining probes of four aza-BODIPY compounds [herein referred to as 7(a−d)]. Compounds 7(b−d) were found to display an outstanding selectivity for Cu(II) b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Miao et al developed various red to near-infrared emitting pyrrolyl BODIPY dyes and demonstrated good lipophilic character, excellent photostability, low cytotoxicity and intense NIR fluorescence of fluorophore pyrrolylBODIPY (Figure 2) in the mitochondrial of HeLa cells [45]. Rivero and co-workers synthesized, characterized, and evaluated different aza-BODIPY compounds as metal sensors and cell staining probes and they found aza-BODIPY (Figure 2) allowed them to characterize a lipotoxic condition mediated by saturated fatty acids, a critical phenomenon on β-cell damage associated with diabetes mellitus type II [46]. Wang et al synthesized and studied a series of mono-spiro-and di-amino acid−BODIPY derivatives, containing basic (histidine, lysine, and arginine), acidic (aspartic acid), polar (tyrosine, serine, and glutamine), and nonpolar (methionine) amino acid residues for potential therapeutic and/or imaging applications [47].…”
Section: Bodipy-based Fluorescent Compoundsmentioning
confidence: 99%
“…Miao et al developed various red to near-infrared emitting pyrrolyl BODIPY dyes and demonstrated good lipophilic character, excellent photostability, low cytotoxicity and intense NIR fluorescence of fluorophore pyrrolylBODIPY (Figure 2) in the mitochondrial of HeLa cells [45]. Rivero and co-workers synthesized, characterized, and evaluated different aza-BODIPY compounds as metal sensors and cell staining probes and they found aza-BODIPY (Figure 2) allowed them to characterize a lipotoxic condition mediated by saturated fatty acids, a critical phenomenon on β-cell damage associated with diabetes mellitus type II [46]. Wang et al synthesized and studied a series of mono-spiro-and di-amino acid−BODIPY derivatives, containing basic (histidine, lysine, and arginine), acidic (aspartic acid), polar (tyrosine, serine, and glutamine), and nonpolar (methionine) amino acid residues for potential therapeutic and/or imaging applications [47].…”
Section: Bodipy-based Fluorescent Compoundsmentioning
confidence: 99%
“…toxicity, and excellent photo stability [20][21][22][23][24][25][26][27]. Previously, we reported a BF2-azadipyrromethene of general structure A as a lysosomal acidity off-to-on responsive probe with excellent photostabilities, good quantum yields, and no phototoxicity at concentrations used for imaging (Figure 1) [28].…”
Section: Introductionmentioning
confidence: 96%
“…Introduced in the early 2000s, the BF 2 -azadipyrromethenes are an exciting near-infrared (NIR) emissive platform from which application-specific imaging agents can be constructed [ 17 , 18 , 19 ]. They are ideally suited to both live cellular and in vivo imaging, with fluorescence wavelengths tunable within the low-level energy range of 650 to 850 nm, low toxicity, and excellent photo stability [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. Previously, we reported a BF 2 -azadipyrromethene of general structure A as a lysosomal acidity off-to-on responsive probe with excellent photostabilities, good quantum yields, and no phototoxicity at concentrations used for imaging ( Figure 1 ) [ 28 ].…”
Section: Introductionmentioning
confidence: 99%